Principal’s coaching strategy in developing teachers’ pedagogical competence - Fatmawati Fatmawati; Hairida Hairida; Marinu Waruwu; Eny Enawati; Henny Sanulita (ARKA INSTITUTE, 2026)
This study aims to describe the principal’s coaching strategy in developing teachers’ pedagogical competence at SMA Negeri 3 Sanggau, to identify supporting and inhibiting factors, and to analyze its impact on teaching and learning. The research employed a qualitative approach with a case study design. Informants involved included the principal, vice principal for curriculum, six teachers, and two students. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings show that the coaching strategy was implemented through the stages of pre-supervision, observation, and post-supervision, emphasizing reflection, collaborative dialogue, and constructive feedback. Supporting factors included the principal’s supportive leadership, an open school culture, and educational policy support. The main obstacles were teacher resistance, limited time, and lack of understanding of the coaching concept.The impact of coaching was evident in the improvement of teachers’ pedagogical competence, particularly in understanding learning concepts, designing interactive learning, and conducting reflective evaluation. This study highlights the importance of the principal’s role as a coach in academic supervision to create effective and sustainable learning.